Planos municipais de educação: as interfaces da caminhada de construção - Assumpção, Eracilda de (Universidade do Vale do Rio do Sinos, 2006)
The research analyzes, with basis in the historical trajectory of construction of the Educational Plans, the form as the same ones are projected, idealized and constructed by the educative community and the civil society. We begin our quarrels, covering the legislation in vigor, as the Federal Constitution from 1988, the Law of guidelines and Bases of the National Education n° 9394/96, the National Education plan, the State Plan Educational Rio Grande do Sul state, the State Law of the Democratic Management of the Education n° 10,576 of 14/11/1995, as well as the interaction through the readings of theoreticians who converge to the field of the quarrels, in which we insert, joining the terms of the equation to that we had already described, having as makers theoreticians authors as: Arroyo (1997, 2003), Assmann (1999), Bobbio (1997, 2001), Calame and Talmant (2001), Cury (1999,2000), Delors (1999), Demo (1993, 1996, 2000), Santos (2000), among others, who had given sustentation for the presented arguments. T
Keywords: educação municipal; política educacional; planejamento municipal; Rio Grande do Sul; educational politics; municipal education; municipal planning; Ciências Humanas